Principles of Research Framework and Methodology: A Critical Assessment - Ehsan, Muhammad Asif (IJRDO- Journal of Educational Research, 2017)
Research involves a series of judicious and carefully executed activities that enable the researcher to know how problems can be solved or at least considerably minimized. Ergo, it embodies the processes of inquiry, investigation, examination and experimentation. These processes have to be carried out systematically, diligently, critically, objectively and logically. The anticipated end results help the researchers to deal with the problem. The paper dilates on the proposition that a problem does not necessarily mean that something is seriously wrong with a current situation that needs to be rectified immediately. A problem could simply indicate an interest in an issue where finding the right answers might help to improve an existing situation. Methodology, on the other hand, is driven by certain ontological and epistemological assumptions, and consists of research questions or hypotheses, a conceptual approach to a topic, the methods to be used in the study and consequently the data sources. All of these components are inextricably linked to one another in a logical manner. The paper canvasses quantitative and qualitative researches which constitute different approaches to social investigation. Various studies such as exploratory, descriptive and explanatory are discussed into the bargain.